The innominate injunction: quintessential of the access to justice - Jiménez-Martínez, María Juliana; Rodriguez-Pardo, Diego Fernando; Santos Young, Erick Esleider; Murillo-Romero, David Camilo; Hernández-Guzman, Geraldi; Galindo-Cuadros, Diana Alejandra; Rivera-Estupiñan, Clara Natalia; Quintero-Rodríguez, Carolina; Quiroga-Rodríguez, Paula Andrea; Reyes, Fanny Mayerly; Porras-López, Edizon Gonzalo (Universidad Pedagógica y Tecnológica de Colombia, 2014)
The purpose of this paper lies in highlighting the legal and procedural logic that responds precautionary measure as an instrument of justice, procedural claim and social credibility; perceiving the process as a tool to reach the Justice through the truth, where unnamed precautionary measures emanating from the exactions and thirst for legitimacy, enforceability and effectiveness of judicial decisions, proposing as a result of this, the extent of innominativo to administrative proceedings, by extending the authority of the judge Generic precautionary developing a discretion characterized by proportionality in the classification of the measure, concluding that these tools are the only way to achieve the strengthening of prudential system social credibility in the effectiveness of enforcement of judgments, conclusions drawn through a systematic and comprehensive method.